2015
DOI: 10.1007/s00540-015-2037-5
|View full text |Cite
|
Sign up to set email alerts
|

Airway management in patients undergoing emergency Cesarean section

Takashi Asai

Abstract: Special care is required for airway management of patients undergoing emergency Cesarean section. Although the incidence of difficult intubation and difficult ventilation is similar between pregnant and non-pregnant women, the severity of complications in pregnant patients would be much greater than in non-pregnant patients, if tracheal intubation is found to be difficult: increased risk of pulmonary aspiration, hypoxia, airway obstruction due to laryngeal edema, and a "sleeping baby" being taken out. Rapid-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(75 reference statements)
0
7
0
1
Order By: Relevance
“…However, ESA for CS has been associated with unsatisfactory outcomes, including conversion to another anesthetic method or failure to achieve a satisfactory block (1.7–38%) [1234]. General anesthesia (GA) or spinal anesthesia (SA) after failure of ESA have potential problems such as airway difficulty or high SA [56]. …”
Section: Introductionmentioning
confidence: 99%
“…However, ESA for CS has been associated with unsatisfactory outcomes, including conversion to another anesthetic method or failure to achieve a satisfactory block (1.7–38%) [1234]. General anesthesia (GA) or spinal anesthesia (SA) after failure of ESA have potential problems such as airway difficulty or high SA [56]. …”
Section: Introductionmentioning
confidence: 99%
“…It is not clear whether tracheal intubation using a videolaryngoscope is less likely to traumatize the airway or to prolong apnea time, both of which may lead to serious airway complications [22]. Clarification of these would establish the true role of videolaryngoscopes in patients with difficult airways, particularly in patients receiving rapidsequence induction of anesthesia and in those undergoing emergency Cesarean section [27,28].…”
Section: Adequate Planningmentioning
confidence: 99%
“…It is generally believed that overweight and obese individuals are at greater risk of many complications after surgery, but most perioperative studies have found that this is not the case. [1][2][3] In fact, mildly obese and overweight patients tend to have better survival rates than normal weight patients after many types of surgery, [4][5][6][7][8][9] despite some evidence of increased surgical site and other infections, 1 2 7 10-12 blood loss, 7 12 acute kidney injury, 13 and perhaps other complications. 14 Over the last decade or so, this 'obesity paradox', 6 has also been reported in medical conditions such as coronary artery disease, heart failure, peripheral arterial disease, hypertension, stroke, and renal failure.…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…1 2 In addition, in women undergoing emergency Caesarean section, failure of tracheal intubation increases the risk of hypoxia of both the mother and the baby, unwanted delivery of anaesthetic drugs to the foetus, and the delay in taking the baby out. 3 Rigid indirect-optical laryngoscopes (or 'videolaryngoscopes') generally provide better views of the glottis than with a Macintosh laryngoscope, and thus they are potentially useful to facilitate smooth tracheal intubation. 4 5 In this issue, Komasawa and colleagues 6 have reported a 'disappointing' finding that tracheal intubation using a videolaryngoscope becomes more difficult during rapid-sequence induction of anaesthesia.…”
mentioning
confidence: 99%